Green Synthesis of Copper Nanoparticles Using Gynura procumbens Leaf Extract as a Bioreductant and Their Antibacterial Activity Against Escherichia coli - Nancy Rivana; Suyatno Sutoyo; Radita Yuniar Arizandy; Wahyu Setyarini (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2026)
Copper nanoparticles (CuNPs) are nanomaterials extensively utilized in optics, electronics, biology, catalysis, and as antibacterial agents. Sustainable synthesis approaches employing plant-derived bioreductants have garnered significant attention. In this study, CuNPs were synthesized via green chemistry using Gynura procumbens leaf extract as a bioreductant. Synthesis was performed by combining the leaf extract with 0.1 M CuSO₄ solution at volume ratios of 1:1, 1:2, 1:3, and 1:4. The mixture with the optimal volume ratio was further optimized at pH values of 8, 9, 10, and 11. The resulting CuNPs were characterized by UV-Vis spectroscopy, FTIR, and PSA. Antibacterial activity against Escherichia coli (ATCC 25922) was evaluated using the disk diffusion method. Optimal synthesis was achieved at a 1:2 volume ratio and pH 8. The CuNPs exhibited a maximum UV-Vis absorption at 316 nm, an average particle size of 8.23 nm, and a polydispersity index of 0.1631. FTIR spectra confirmed Cu–O bond vibrations at 457.64 and 617.14 cm-1. The synthesized CuNPs demonstrated strong antibacterial activity against E. coli, with an inhibition zone diameter of 13.89 ± 0.45 mm. These findings suggest that CuNPs synthesized via green methods using G. procumbens extract as a bioreductant have potential as antibacterial agents, particularly against E. coli.